The relation between neutrophil to lymphocyte ratio and diabetic peripheral neuropathy in type 2 diabetes mellitus - جديد , مها; تغريد قدار; اريج بوبو (Latakia University Journal -Medical Sciences Series, 2022)
Background: Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetes mellitus (DM), 50% of DPN patients may be asymptomatic. Further development of DPN can lead to diabetic foot, ulcers, amputation, sriously affecting the quality of patients life. Therefore, searching for a reliable indicator for early diagnosis of DPN are of most significnce. Research has shown that early microvascular disorders and inflammatory processes play important roles in the occurrence and development of DPN. Neutrophil to lymphocyte ratio (NLR) has a close relationship with cancer, cardiovascular diseases, and diabetic microvascular concurrency diseases. We aimed to investigate the relation between NLR and DPN. Methods: A total of 129 newly diagnosed type 2 diabetes mellitus (T2DM) patients were recruited, including 43 patients without complication (DMgroup) as well as 86 patients complicated with DPN (DPN group). Student t test, Mann- Whiney U test, or x2 test was applied to the data of the 2 groups, including the levels of neutrophils and lymphocytes as well as the NLR values of peripheral blood and other biochemistry indexes, Pearson correlation analysis was used to calculate the correlation of NLR and detected factors. Results: NLR values were remarkably higher in DPN group compared with those of DM group (2,43+1,05 vs 1,31+0,19,P˂0,001), the values of glucose, urea, white blood cells (WBC), neutrophils were higher than in DPN group, whereas the lymphocyte count and haemoglobin of DPN group were lower than that of DM group (P˂0,05). The ROC curve analysis confirmed that the optimal cut –off point, specificity, and sensitivity in diagnosing DPN by NLR were, 1,69, 97,6%, 90,7%, respectively. Conclusion: We showed that NLR is significcantly correlated with DPN, which suggested that NLR may be an independent risk factor of DPN.